PENGARUH KUALITAS KOMUNIKASI DAN PENANGANAN KONFLIK TERHADAP CUSTOMER RELATIONSHIP MARKETING: Studi Pada PT. BPR Rudo Indobank - Prasetyo, Agus; Adriyanto, Andhy Tri (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
Research on the Influence of Communication Quality and Conflict Management on Customer Relationship Marketing aims to find out the influence of The Influence of Communication Quality and Conflict Management on Customer Relationship Marketing as Variable Intervening Research Location PT. Bpr Rudo Indobank in Semarang City. The population used is PT Customer. Rudo Indobank. The sample was 100 respondents. Research data comes from two sources, namely primary data and secondary data. This type of research is quantitative. Sampling using purposive random sampling techniques. The collected data is then analyzed using Structural Equation Modelling (SEM) with AMOS 24 software. The results of this research Communication Quality has a significant positive effect on Customer Relationship Marketing, Conflict Management has a significant positive effect on Customer Relationship Marketing.